Kokum: The purple pulse of the Konkan - Rane, Prabhanjan; Prakash, Jai; Korgaonkar, Gopal; Ranjan, Pragya; Srivastava, Vartika (Indian Horticulture, 2025)
Kokum (Garcinia indica Choisy), an underutilized fruit spice from the Western Ghats of India, shows strong potential as a functional food due to its rich phytochemicals and therapeutic effects. Traditionally grown in homesteads and mixed cropping systems of Maharashtra, Goa, Karnataka, and Kerala, kokum is a natural source of hydroxycitric acid, garcinol, and anthocyanins with antioxidant,anti-obesity, and cardiotonic benefits. Products such as kokum syrup, agal, amsul, butter, and tea are staples in regional cuisine and are gaining nutraceutical and cosmetic applications. Despite constraints in postharvest handling and value chains, varietal improvements and value-added products highlight kokum is growing agro-industrial promise.